2017
DOI: 10.1021/acsnano.7b03616
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase Segregation of Self-Assembled Monolayers on Gold Nanoparticles

Abstract: Nanophase segregation of a bi-component thiol self-assembled monolayer is predicted using atomistic molecular dynamics simulations and experimentally confirmed. The simulations suggest the formation of domains rich in acid-terminated chains, on one hand, and of domains rich in amide-functionalized ethylene glycol oligomers, on the other hand. In particular, within the amide-ethylene glycol oligomers region, a key role is played by the formation of inter-chain hydrogen bonds. The predicted phase segregation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 66 publications
(138 reference statements)
3
39
0
Order By: Relevance
“…In situ characterizations, like NAP-XPS and TEM 31 will be pertinent in this context, but again the example of gold particles draws future guidelines to understand hybrid interfaces, especially the organic layer composition and the ligands distribution, by Nuclear Magnetic Resonance 56 and electron tomography 57 coupled to Density Functional Theory calculations and molecular dynamic simulations. 56,57…”
Section: Understanding and Tuning Surface Statesmentioning
confidence: 99%
“…In situ characterizations, like NAP-XPS and TEM 31 will be pertinent in this context, but again the example of gold particles draws future guidelines to understand hybrid interfaces, especially the organic layer composition and the ligands distribution, by Nuclear Magnetic Resonance 56 and electron tomography 57 coupled to Density Functional Theory calculations and molecular dynamic simulations. 56,57…”
Section: Understanding and Tuning Surface Statesmentioning
confidence: 99%
“…A more elegant and scalable strategy to desymmetrize the scaffolds is to exploit specific interactions in ligand-modified nanoparticles in order to induce the formation of surface patterns. [28][29][30][31] The ability to control surface pattern formation on polymercoated nanoparticles recently received much focus in the polymer science community. 32,33 For example, constrained de-wetting of homopolymer ligands under bad solvent conditions had been demonstrated as a versatile paradigm in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…This result agrees with our earlier findings, stating that the Au−S binding energy is expected to be related to the sulfur hybridization. 30,32,54 Concerning the effect of the thiol adsorption on the Au(111) surface, a precursor state for the formation of an adatom can be seen (Figure 7). STM measurements and theoretical calculations showed that the S-CC assembly is more stable than S-CH 3 assembly.…”
Section: ■ Computational Resultsmentioning
confidence: 99%
“…5 This finding does not include entropic considerations to stabilization/formation, which are expected to be of similar magnitude for all SAMs because of the similar physicochemical properties of both thiol derivatives. 30,32,54 Furthermore, the binding energy (2.6 eV) was calculated to be constant throughout the mixture series. This result agrees with our earlier findings, stating that the Au−S binding energy is expected to be related to the sulfur hybridization.…”
Section: ■ Computational Resultsmentioning
confidence: 99%
See 1 more Smart Citation